Uncoupling the structure–activity relationships of β2 adrenergic receptor ligands from membrane binding - Dickson, Callum J.; Hornak, Victor; Velez-Vega, Camilo; McKay, Daniel J.J.; Reilly, John; Sandham, David A.; Shaw, Duncan; Fairhurst, Robin A.; Charlton, Steven J.; Sykes, David A.; Pearlstein, Robert; Duca, Jose S. (American Chemical Society, 2016)
Ligand binding to membrane proteins may be significantly influenced by the interaction of ligands with the membrane. In particular, the microscopic ligand concentration within the membrane surface solvation layer may exceed that in bulk solvent, resulting in overestimation of the intrinsic protein−ligand binding contribution to the apparent/measured affinity. Using published binding data for a set of small molecules with the β2 adrenergic receptor, we demonstrate that deconvolution of membrane and protein binding contributions allows for improved structure−activity relationship analysis and structure-based drug design. Molecular dynamics simulations of ligand bound membrane protein complexes were used to validate binding poses, allowing analysis of key interactions and binding site solvation to develop structure−activity relationships of β2 ligand binding. The resulting relationships are consistent with intrinsic binding affinity (corrected for membrane interaction). The successful structure-based design of ligands targeting membrane proteins may require an assessment of membrane affinity to uncouple protein binding from membrane interactions.